2020
DOI: 10.33805/2573.3877.147
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Workshop on Hand Washing Techniques among Undergraduate Nursing Students: A Quasi Experimental Study

Abstract: Background: Compliance with the performance of correct and effective hand hygiene has not been adequate among undergraduate nursing students, in clinical settings. Aim: That is why this study evaluated if a hand washing workshop can effectively enhance the performance of hand washing among undergraduate nursing students. Method: A total of 15 participants were enrolled from a group of undergraduate nursing students; selected using simple random sampling. These participants primarily did a workshop on the 12-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Studies have also reported a decreased compliance in hand hygiene over time among the auxiliaries who were not regularly trained or had workshops, indicating the importance of these refresher courses. 24,25 In the present study, 71.3% of the respondents reported that they were regularly trained, whereas, 55% of the auxiliaries revealed that they have not received any workshops on hand hygiene in the past two years. In contrast to private institutes, public institutes lack regular hand hygiene training and workshops for their auxiliaries.…”
Section: Discussionmentioning
confidence: 51%
“…Studies have also reported a decreased compliance in hand hygiene over time among the auxiliaries who were not regularly trained or had workshops, indicating the importance of these refresher courses. 24,25 In the present study, 71.3% of the respondents reported that they were regularly trained, whereas, 55% of the auxiliaries revealed that they have not received any workshops on hand hygiene in the past two years. In contrast to private institutes, public institutes lack regular hand hygiene training and workshops for their auxiliaries.…”
Section: Discussionmentioning
confidence: 51%